Absorção e distribuição do nitrogênio em videiras cv. Niagara Rosada, em função do porta-enxerto e de adubos verdes - Reis Junior, João de Ribeiro (2012)
Green manures cultivation has become an important option for recycling nutrients in organic cropping. However, its benefits are often not obtained in the short term. The aim of this study was to determine whether the use of cover crops in the winter can contribute to the provision of N for the vine plant. Two experiments were carried out. The first one sought to quantify the N in green manure species (Lupinus albus, Pisum arvense, Vicia sativa, Vicia villosa, Triticale hexaploide, Avena sativa, Lollium multiflorum e Raphanus sativus). The second experiment aimed to evaluate the use of N by `Niagara Rosada` vine on two rootstocks (IAC-572 `Jales` and IAC 766 `Campinas`), and its distribution in the plant, from five sources of N, using the 15N tracer technique. Experiments were conducted in a greenhouse with a soil collected from 20 to 40 layer cm classified as Latosol. The first stage of the experiment was conducted with the aim of isotopic labeling of green manure, using ammonium sulfate enriched at 10% of 15N atoms. Green manures were grown in pots containing 4 L of soil in a randomized block experimental design with 8 treatments, 4 replicates and the plot was constituted by a pot. In the second stage pots containing 14 L of soil were used, where vine cv. Pink Niagara grafted seedlings were planted. The experimental design was randomized blocks in factorial scheme 2 x 5 (2 rootstocks x 4 species of green manure or mineral fertilizer), four replicates and one plant as experimental plot. The results of the first experiment showed that oat was the largest producer of dry matter (11.68 g pot-1). The pea, hairy vetch and common vetch had the lowest C / N ratios, with values of 16, 16 and 18, respectively. Hairy vetch was the most efficient (255.1 mg pot-1) on the accumulation of N and triticale and oat were the species which best used the mineral fertilizer N. In the second experiment, the results showed that the dry matter from the rootstocks roots and the amount of N accumulated in the vines suffered significant treatments effect. The N uptake efficiency varied according to treatment and type of rootstock. The maximum absorption occurred in the N mineral treatment (39.5%), and pea showed the best result (35.2%) among cover crops.